Stakeholders’ perception on early briefing towards the reduction of strata disputes in Melaka - Chong, Kim Guan (2023)
Strata living in strata development has become a new lifestyle trend: good common facilities, common areas, club house, swimming pool, playground, etc. However, the notion of living close to each other and shared facilities may induce inevitable strata disputes. Owing to the rising number, the government has taken more initiatives where Strata management Act 2015 (Act 757) guides stakeholders for better managing strata issues. This research determines to identify the probable strata disputes that can be prevented at the early stage thus examining the level of awareness among strata living regarding the strata disputes, and to recommend the most suitable time to conduct the early briefing so that it can effectively reduce strata disputes; explore early briefing awareness that can reduce the strata disputes hence to seek the best suitable time to conduct the early briefing session. A mixed method approach was conducted where survey research using questionnaires was conducted with residents and in- depth interviews with three subject matter experts in strata management. During two townhall with 80 respondents, indicated the types of strata disputes as well as the awareness on strata disputes based on the opinions of strata living residents. The data was analysed using Descriptive Statistical Analysis in the Statistical Package for Social Sciences (SPSS) software and were then triangulated with thematic analysis. Pearson Correlation was used to determine the level of awareness among strata dwellers on the types of disputes, resolutions, and the Strata Management Act. The results: residents are keen to participate in an early briefing and have demonstrated understanding of the nature of strata living, rules apply in strata management and with property managers as well as shared facilities. Further enquiry made with subject matter expert agrees that early briefing should be done at the earliest to address residents’ concerns hence may reduce probable strata disputes in the future, confirms the results from residents survey. Therefore, it is envisaged that an early briefing approach can be adopted as a new standard practice adopted by property managers to lessen strata disputes in strata development and management